Integrated Analysis Reveals the Characteristics and Effects of SARS-CoV-2 Maternal–Fetal Transmission - Huang, Ziliang; Xia, Shuting; Mei, Shiqiang; Wen, Yanzi; Liu, Jialiu; Dong, Chengzhi; Chen, Wenxin; Yu, Peijie; Qu, Lianghu; Luo, Yanmin; Zheng, Lingling (Frontiers in Microbiology, 2022)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection has caused a pandemic of Coronavirus disease 2019 (COVID-19) and is threatening global health. SARS-CoV-2 spreads by air with a transmission rate of up to 15%, but the probability of its maternal-fetal transmission through the placenta is reported to be low at around 3.28%. However, it’s still unclear that which tissues and developmental periods hold higher risks and what the underlying molecular mechanisms are. We conducted an integrated analysis of large-scale transcriptome and single-cell sequencing data to investigate the key factors that affect SARS-CoV-2 maternal-fetal transmission as well as the characteristics and effects of them. Our results showed that the abundance of cytomegalovirus (CMV) and Zika virus (ZIKV) infection associated factors in the placenta were higher than their primarily infected tissues, while the expression levels of SARS-CoV-2 binding receptor Angiotensin Converting Enzyme II (ACE2) were similar between lung and placenta. By contrast, an important SARS-CoV-2 infection associated factor, Type II transmembrane serine protease (TMPRSS2), was poorly expressed in placenta. Further scRNA-Seq analysis revealed that ACE2 and TMPRSS2 were co-expressed in very few trophoblastic cells. Interestingly, during the embryonic development stages, the abundance of ACE2 and TMPRSS2 was much higher in multiple embryonic tissues than in the placenta. Based on our present analysis, the intestine in 20th week of embryonic development were at a high risk of SARS-CoV-2 infection. Additionally, we found that during the fetal development, ACE2 and TMPRSS2 were enriched in pathogen infection associated pathways and may involve in the biological processes related to T cell activation. In conclusion, our present study suggests that though the placenta provides a good physical barrier against SARS-CoV-2 infection for healthy fetal development, multiple embryonic tissues are under risks of the virus infection, which may be adversely affected once infected prenatally. Therefore, it’s necessary to enhance maternal care to prevent the potential impact and harm of SARS-CoV-2 maternal-fetal transmission.